Policy communication: effectiveness of Chinese dialects - Sam, Wan Ting (Nanyang Technological University, 2024)
This paper explores the effectiveness of Chinese dialects in Singapore’s policy communication towards the elderly through the case studies of locally-produced dialect television shows. The government has sidelined the use of dialects for the benefits of its bilingual language policy. Surprisingly, since 2014, the government has frequently engaged dialects in its policy communication. The government has recognised the importance of policy communication in policy implementation. To which, it is willing to ‘soften’ its stance on the use of dialects. However, there is minimal research done on the effectiveness of dialects despite this surprising move and there is no evaluation done on dialect policy communication. Thus, this paper aims to contribute to the literature in this aspect. Employing the framework of individual and structural barriers of participation by Rubenson and Desjardins (2009), respondents have surfaced that dialects can lower individual barriers of understanding caused by language barriers and reduce elderly’s indifference towards policies. However, it still has to work within legal regulations which is a structural barrier that has restricted the outreach of dialect communication. Respondents also surfaced certain limitations and future challenges which the paper has suggested some refinements to dialect policy communication accordingly. Beyond this case study, this paper hopes for more research to be conducted on policy communication (1) towards elderly of other ethnicities in Singapore and (2) in other Asia multilingual countries for a more comprehensive understanding of policy communication locally and regionally.